Multiple Choice
Which of the following is a solution to the equation y = 3x – 1?
(1 point)
21 answers
There are no options provided to choose from. Please provide the options for a valid answer.
Multiple Choice
Which of the following is a solution to the equation y = 3x – 1?
(1 point)
Responses
(4, 1)
(4, 1)
(2, 5)
(2, 5)
(4, 3)
(4, 3)
(0, –3)
Which of the following is a solution to the equation y = 3x – 1?
(1 point)
Responses
(4, 1)
(4, 1)
(2, 5)
(2, 5)
(4, 3)
(4, 3)
(0, –3)
To determine if a point is a solution to the equation y = 3x - 1, we need to substitute the x and y values for the point into the equation and see if it makes a true statement.
Let's substitute the x and y values of each option into the equation and check:
Option 1: (4, 1)
Substituting x = 4 and y = 1 into y = 3x - 1:
1 = 3(4) - 1
1 = 12 - 1
1 = 11
The equation is not true, so (4, 1) is not a solution.
Option 2: (2, 5)
Substituting x = 2 and y = 5 into y = 3x - 1:
5 = 3(2) - 1
5 = 6 - 1
5 = 5
The equation is true, so (2, 5) is a solution.
Option 3: (4, 3)
Substituting x = 4 and y = 3 into y = 3x - 1:
3 = 3(4) - 1
3 = 12 - 1
3 = 11
The equation is not true, so (4, 3) is not a solution.
Option 4: (0, -3)
Substituting x = 0 and y = -3 into y = 3x - 1:
-3 = 3(0) - 1
-3 = 0 - 1
-3 = -1
The equation is not true, so (0, -3) is not a solution.
Therefore, the only solution is (2, 5).
Let's substitute the x and y values of each option into the equation and check:
Option 1: (4, 1)
Substituting x = 4 and y = 1 into y = 3x - 1:
1 = 3(4) - 1
1 = 12 - 1
1 = 11
The equation is not true, so (4, 1) is not a solution.
Option 2: (2, 5)
Substituting x = 2 and y = 5 into y = 3x - 1:
5 = 3(2) - 1
5 = 6 - 1
5 = 5
The equation is true, so (2, 5) is a solution.
Option 3: (4, 3)
Substituting x = 4 and y = 3 into y = 3x - 1:
3 = 3(4) - 1
3 = 12 - 1
3 = 11
The equation is not true, so (4, 3) is not a solution.
Option 4: (0, -3)
Substituting x = 0 and y = -3 into y = 3x - 1:
-3 = 3(0) - 1
-3 = 0 - 1
-3 = -1
The equation is not true, so (0, -3) is not a solution.
Therefore, the only solution is (2, 5).
Which equation matches the statement: “The sum of –4x and 2 is 9”?
(1 point)
Responses
–4x + 2 = 9
–4 x + 2 = 9
–4x + 9 = 2
–4 x + 9 = 2
–4x(2) = 9
–4 x (2) = 9
–4x – 2 = 9
(1 point)
Responses
–4x + 2 = 9
–4 x + 2 = 9
–4x + 9 = 2
–4 x + 9 = 2
–4x(2) = 9
–4 x (2) = 9
–4x – 2 = 9
The correct equation that matches the statement "The sum of -4x and 2 is 9" is:
–4x + 2 = 9
This equation represents the sum of -4x and 2, which is equal to 9.
–4x + 2 = 9
This equation represents the sum of -4x and 2, which is equal to 9.
Solve. x – 6 = –18
(1 point)
Responses
x = –24
x = –24
x = –12
x = –12
x = 12
x = 12
x = 6
(1 point)
Responses
x = –24
x = –24
x = –12
x = –12
x = 12
x = 12
x = 6
To solve the equation x - 6 = -18, we can add 6 to both sides of the equation to isolate the variable x.
x - 6 + 6 = -18 + 6
This simplifies to:
x = -12
Therefore, the solution to the equation x - 6 = -18 is x = -12.
x - 6 + 6 = -18 + 6
This simplifies to:
x = -12
Therefore, the solution to the equation x - 6 = -18 is x = -12.
Solve. 4x + 3 = 47
(1 point)
Responses
x = 11
x = 11
x = 40
x = 40
x = 44
x = 44
x = 50
(1 point)
Responses
x = 11
x = 11
x = 40
x = 40
x = 44
x = 44
x = 50
To solve the equation 4x + 3 = 47, we can subtract 3 from both sides of the equation to isolate the variable x.
4x + 3 - 3 = 47 - 3
This simplifies to:
4x = 44
Then, we divide both sides of the equation by 4 to solve for x:
4x/4 = 44/4
x = 11
Therefore, the solution to the equation 4x + 3 = 47 is x = 11.
4x + 3 - 3 = 47 - 3
This simplifies to:
4x = 44
Then, we divide both sides of the equation by 4 to solve for x:
4x/4 = 44/4
x = 11
Therefore, the solution to the equation 4x + 3 = 47 is x = 11.
Solve. one-thirdx = 12
(1 point)
Responses
x = 4
x = 4
x = 15
x = 15
x = 36
x = 36
x = 39
x = 39
(1 point)
Responses
x = 4
x = 4
x = 15
x = 15
x = 36
x = 36
x = 39
x = 39
To solve the equation one-thirdx = 12, we need to isolate the variable x.
Since we have one-third times x equals 12, we can multiply both sides of the equation by 3 to get rid of the fractional coefficient:
3 * (one-thirdx) = 3 * 12
x = 36
Therefore, the solution to the equation one-thirdx = 12 is x = 36.
Since we have one-third times x equals 12, we can multiply both sides of the equation by 3 to get rid of the fractional coefficient:
3 * (one-thirdx) = 3 * 12
x = 36
Therefore, the solution to the equation one-thirdx = 12 is x = 36.
Solve. Start Fraction 3 over 2 End Fractionx – 4 = 16
(1 point)
Responses
x = 20
x = 20
x = 13 start fraction 1 over 3 end fraction
x = 13 Image with alt text: start fraction 1 over 3 end fraction
x = 15 start fraction 1 over 3 end fraction
x = 15 Image with alt text: start fraction 1 over 3 end fraction
30
(1 point)
Responses
x = 20
x = 20
x = 13 start fraction 1 over 3 end fraction
x = 13 Image with alt text: start fraction 1 over 3 end fraction
x = 15 start fraction 1 over 3 end fraction
x = 15 Image with alt text: start fraction 1 over 3 end fraction
30
To solve the equation (3/2)x - 4 = 16, we can first add 4 to both sides of the equation to isolate the variable x.
(3/2)x - 4 + 4 = 16 + 4
This simplifies to:
(3/2)x = 20
To get rid of the fraction, we can multiply both sides of the equation by 2/3:
(2/3) * (3/2)x = (2/3) * 20
This simplifies to:
x = 40/3
The fraction 40/3 can also be expressed as a mixed number. After dividing 40 by 3, the quotient is 13 with a remainder of 1.
Therefore, the solution to the equation is x = 13 1/3.
(3/2)x - 4 + 4 = 16 + 4
This simplifies to:
(3/2)x = 20
To get rid of the fraction, we can multiply both sides of the equation by 2/3:
(2/3) * (3/2)x = (2/3) * 20
This simplifies to:
x = 40/3
The fraction 40/3 can also be expressed as a mixed number. After dividing 40 by 3, the quotient is 13 with a remainder of 1.
Therefore, the solution to the equation is x = 13 1/3.
Solve. Start Fraction 3 over 2 End Fractionx – 4 = 16
To solve the equation (3/2)x - 4 = 16, we can first add 4 to both sides of the equation to isolate the variable x.
(3/2)x - 4 + 4 = 16 + 4
This simplifies to:
(3/2)x = 20
To get rid of the fraction, we can multiply both sides of the equation by 2/3:
(2/3) * (3/2)x = (2/3) * 20
This simplifies to:
x = 40/3
The fraction 40/3 can also be expressed as a decimal. After dividing 40 by 3, the quotient is 13.3333 (rounded to four decimal places).
Therefore, the solution to the equation is x = 13.3333 (or approximately x = 13.33).
(3/2)x - 4 + 4 = 16 + 4
This simplifies to:
(3/2)x = 20
To get rid of the fraction, we can multiply both sides of the equation by 2/3:
(2/3) * (3/2)x = (2/3) * 20
This simplifies to:
x = 40/3
The fraction 40/3 can also be expressed as a decimal. After dividing 40 by 3, the quotient is 13.3333 (rounded to four decimal places).
Therefore, the solution to the equation is x = 13.3333 (or approximately x = 13.33).
Use the given equation to find the solution to the following problem.
The equation 9.95 + 0.30s = c gives the cost c in dollars that a website charges for downloading songs. The variable s stands for the number of songs downloaded. Find the cost of downloading 35 songs.
(1 point)
Responses
c = $9.95
c = $9.95
c = $20.45
c = $20.45
c = $35.00
c = $35.00
c = $114.45
c = $114.45
The equation 9.95 + 0.30s = c gives the cost c in dollars that a website charges for downloading songs. The variable s stands for the number of songs downloaded. Find the cost of downloading 35 songs.
(1 point)
Responses
c = $9.95
c = $9.95
c = $20.45
c = $20.45
c = $35.00
c = $35.00
c = $114.45
c = $114.45
To find the cost of downloading 35 songs, we need to substitute s = 35 into the given equation 9.95 + 0.30s = c.
9.95 + 0.30(35) = c
9.95 + 10.50 = c
20.45 = c
Therefore, the cost of downloading 35 songs is c = $20.45.
9.95 + 0.30(35) = c
9.95 + 10.50 = c
20.45 = c
Therefore, the cost of downloading 35 songs is c = $20.45.
10 of 1010 of 10 Items
Question
Write an equation and solve to find the solution to the following problem.
You have $27 to spend at the mall and a coupon for $6 off at your favorite store. A t-shirt costs $11. How many t-shirts can you buy using your coupon and money?
(1 point)
Question
Write an equation and solve to find the solution to the following problem.
You have $27 to spend at the mall and a coupon for $6 off at your favorite store. A t-shirt costs $11. How many t-shirts can you buy using your coupon and money?
(1 point)
Let x be the number of t-shirts you can buy.
The cost of each t-shirt is $11, and you have a coupon for $6 off. So the effective cost of each t-shirt will be $11 - $6 = $5.
You have $27 to spend, so the equation can be written as:
5x = 27
To solve for x, divide both sides of the equation by 5:
x = 27 / 5
x ≈ 5.4
Since you can't buy a fraction of a t-shirt, you can only buy a whole number of t-shirts. So the maximum number of t-shirts you can buy is 5.
The cost of each t-shirt is $11, and you have a coupon for $6 off. So the effective cost of each t-shirt will be $11 - $6 = $5.
You have $27 to spend, so the equation can be written as:
5x = 27
To solve for x, divide both sides of the equation by 5:
x = 27 / 5
x ≈ 5.4
Since you can't buy a fraction of a t-shirt, you can only buy a whole number of t-shirts. So the maximum number of t-shirts you can buy is 5.
SORRY THATS WRONG THE ANSWERS ARE
1 shirt
1 shirt
2 shirts
2 shirts
3 shirts
3 shirts
4 shirts
1 shirt
1 shirt
2 shirts
2 shirts
3 shirts
3 shirts
4 shirts
I apologize for the incorrect response.
Let's solve the problem correctly:
To find the number of t-shirts you can buy, we need to take into account the $6 coupon and the cost of each t-shirt, which is $11.
We can set up the equation as:
$11x - $6 = $27
To solve for x, we need to get rid of the $6 coupon by adding it to both sides of the equation:
$11x = $27 + $6
$11x = $33
Finally, we divide both sides of the equation by $11 to solve for x:
x = $33 / $11
x = 3
Therefore, you can buy 3 t-shirts with your $27 budget and the $6 coupon.
Let's solve the problem correctly:
To find the number of t-shirts you can buy, we need to take into account the $6 coupon and the cost of each t-shirt, which is $11.
We can set up the equation as:
$11x - $6 = $27
To solve for x, we need to get rid of the $6 coupon by adding it to both sides of the equation:
$11x = $27 + $6
$11x = $33
Finally, we divide both sides of the equation by $11 to solve for x:
x = $33 / $11
x = 3
Therefore, you can buy 3 t-shirts with your $27 budget and the $6 coupon.